Editorial - Faisal Jamil, PhD (NUST Journal of Social Sciences and Humanities)
Climate change is upon us all and its impact is not gender neutral. The climate crisis exacerbates existing inequalities, disproportionately affecting vulnerable populations due to intersecting factors like gender, age, race, class and poverty. For instance, rising temperatures and rainfall patterns invariably affect everyone, though some people are more severely impacted due to their intrinsic vulnerabilities. Women especially those belonging to poor households and disadvantaged race and class face unique threats. Interestingly, women are at the forefront of facing the threats and taking climate action, but discriminatory power structures limit their representation in decision-making process.